1976
DOI: 10.1029/gl003i005p00265
|View full text |Cite
|
Sign up to set email alerts
|

Combustion as a source of nitrous oxide in the atmosphere

Abstract: Recent measurements of the exhaust gases in the stacks of power plants burning coal and natural gas have shown high levels of nitrous oxide. Calculations based upon the known combustion parameters of the power plants and extrapolated to the current world production of coal and natural gas indicate that combustion may be a significant source of nitrous oxide in the atmosphere. In view of the predicted increases in the combustion of fossil fuels, particularly coal, it is likely that the importance of combustion … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
24
0

Year Published

1978
1978
2001
2001

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 106 publications
(24 citation statements)
references
References 6 publications
0
24
0
Order By: Relevance
“…In fact, several authors have deduced a long-term trend of increasing N20 mixing ratios in the troposphere being in the range of 0.2-0.3% (Weiss, 1981;Khalil and Rasmussen, 1983;Robinson et al, 1984). This increase is thought to be due to usage of mineral nitrogen fertilizers (Crutzen and Ehhalt, 1977;McElroy et al, 1977;Liu et al, 1977) to combustion of fossil fuel (Pierotti and Rasmussen, 1976;Weiss and Craig, 1976) and to biomass burning (Crutzen et al, 1979;1985). All these sources show increasing trends of their production rates during the last decades because of man's activity and, therefore, will have an increasing impact on the atmospheric N20 burden.…”
Section: Introductionmentioning
confidence: 99%
“…In fact, several authors have deduced a long-term trend of increasing N20 mixing ratios in the troposphere being in the range of 0.2-0.3% (Weiss, 1981;Khalil and Rasmussen, 1983;Robinson et al, 1984). This increase is thought to be due to usage of mineral nitrogen fertilizers (Crutzen and Ehhalt, 1977;McElroy et al, 1977;Liu et al, 1977) to combustion of fossil fuel (Pierotti and Rasmussen, 1976;Weiss and Craig, 1976) and to biomass burning (Crutzen et al, 1979;1985). All these sources show increasing trends of their production rates during the last decades because of man's activity and, therefore, will have an increasing impact on the atmospheric N20 burden.…”
Section: Introductionmentioning
confidence: 99%
“…Weiss and Craig, 11 Pierotti and Rasmussen, 12 Hao et al, 10 and Castaldini et al, 13 have all reported N2O measurements from stationary combustion systems, such as utility and industrial boilers. The results of these studies indicate that systems fired with natural gas do not produce significant concentrations of N2O.…”
mentioning
confidence: 99%
“…Nitrous oxide is believed to originate as a by-product of microbiological activity at and near the earth's surface (Bates and Witherspoon, 1952;Bates and Hays, 1967), and concern has arisen in recent years that a variety of human activities might lead to a significant increase in the net global source of atmospheric N 2 O (Crutzen, 1974;McElroy, 1974;Pierotti and Rasmussen, 1976;Weiss and Craig, 1976).…”
mentioning
confidence: 99%